Childhood cancer survivors: current challenges - M. Angeles Vázquez López (Elsevier, 2024)
Rates of childhood cancer survival in developed countries have risen to over 80-85 %. In consequence, the population of childhood cancer survivors (CCS) has grown considerably. Nevertheless, CCS present a high morbidity and mortality due to cancer or its treatment, with an increased risk of premature mortality, second primary tumors and late side effects, both physical and psychosocial, all of which decrease the quality of life. Long-term follow-up (LTFU) of CCS is recommended to prevent, detect and treat those health problems. Despite the advances achieved, the management of CCS is still not optimal. Among the areas for improvement discussed in this manuscript are: (1) Quantifying the real burden of morbimortality, by implementing new frequency measures (mean cumulative count and cumulative burden), to obtain more accurate assessments, and using simulation models, to determine individual risks; (2) Assessing the impact of risk factors for late side effects, related to the patient, tumor type, treatments, lifestyle, comorbidities, genetics and ageing; (3) Considering the impact of the international harmonisation of long-term follow-up guidelines, to generate homogeneous, evidence-based recommendations and an individualized LTFU and, (4) Challenges to LTFU implementation, considering models of care adapted to patient risk and needs, with special attention to the transition to adult-care follow-up. Finally, we comment on the situation of CCS in Spain and consider future prospects for improving the health and quality of life of this population. Resumen: La supervivencia del cáncer infantil supera en la actualidad el 80-85 % en países desarrollados. La población superviviente ha crecido considerablemente, presentando una elevada morbimortalidad secundaria al cáncer o su tratamiento, representada por un riesgo incrementado de mortalidad prematura, segundos tumores y efectos tardíos (ET), en la esfera física y psicosocial, afectando la calidad de vida. El seguimiento a largo plazo y de por vida en supervivientes de cáncer infantil (SCI), está recomendado para prevenir, detectar y tratar sus problemas de salud. A pesar de los avances producidos, el manejo de los SCI no es adecuado. En este artículo se plantean los retos pendientes como: (1) Cuantificar la carga real de morbimortalidad, proponiendo nuevas medidas de frecuencia (recuento acumulado medio y carga acumulada), que ofrecen resultados más exactos de la multimorbilidad que presentan, y la utilización de modelos de simulación, para conocer el riesgo individual de eventos; (2) Impacto de factores que determinan el riesgo de presentar ET relacionados con el paciente, tumor, tratamientos, estilo de vida, comorbilidades, genética y envejecimiento; (3) Importancia de la armonización de las guías de seguimiento a largo plazo a nivel mundial, para ofrecer recomendaciones homogéneas, basadas en la evidencia y un plan individualizado de seguimiento y (4) Problemas en la implementación del seguimiento, con diferentes modelos de atención, adaptados al riesgo y necesidades del paciente, con especial atención a la transición. Finalmente, se comenta la situación actual de los SCI en España y consideramos las perspectivas futuras que contribuyan a mejorar la salud y calidad de vida de esta población.